Purposes of sharee'ah and its relationship with the financial field - El-Seoudi, Abdel Wadoud Moustafa Moursi; Mohd Nor, Amir Husin; Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Laluddin, Hayatullah; Ibrahim, Ibnor Azli; Samsudin, Muhammad Adib; Alias, Muhammad Nazir (Medwell Journal, 2012)
What is meant by the objectives of Sharee'ah (Islamic revealed laws) is the results, effects and fruits that the religion aim to achieve and reach through the application of the rulings. Maqaasid is linguistically derived from the Arabic root qasd and maqsad and both of them are derived from the Arabic verb qasada whcih means adopting the straight, fair and moderate way. According to the technical meaning, Maqaasid Ash-Sharee'ah refers to the meanings and rulings that Lawgiver aims to achieve through His legislations and rulings which the mujtahid scholars derive from the religious texts. Objectives of Sharee'ah has a close relationship with the field of funds. Considering the objectives of Sharee'ah in the financial field in Islam does not differ from its status and ruling in all the other chapters of fiqh (Islamic jurisprudence). Also, juristic reasoning applies to both of them. The objectives that will be discussed in this research and its relationship with the field of funds are the objectives of the wise Lawgiver in the funds, i.e., what Allaah The Almighty wanted to be achieved from His words and rulings in the financial filed in Islam. This research is talking about the objectives of Sharee'ah, its divisions, its close relationship with the field of funds as well as discussing the Islamic institutions represented in the Islamic banks and the extent of their achievement of the objectives of the Islamic Sharee'ah. © Medwell Journals, 2012.